Spontaneous left coronary artery dissection in the postpartum period: a case report - A. A. Kuznetsov; A. M. Namitokov; A. V. Sazhneva; A. S. Nekrasov; E. D. Kosmacheva (Российский кардиологический журнал)
Spontaneous coronary artery dissection is a rare disease that threatens the patient life. Often this pathology complicates the course of pregnancy or the postpartum period. The rare occurrence and difficulties in diagnosis are the reason for the lack of data and the impossibility of developing a single algorithm for diagnosing and treating spontaneous coronary artery dissection.The article provides a brief literature review and a case report of spontaneous coronary artery dissection in the postpartum period, and discusses a number of aspects of treatment tactics.